Dynamics of the phytoplankton community in Navigation Pool No. 7 of the Upper Mississippi River - Huff, Donald Ross (My University, 1983)
A study of the phytoplankton community dynamics was conducted on Navigation Pool No. 7 of the Upper Mississippi River from May through October 1982. The objectives of this study were to estimate total standing crops, determine the taxonomic compoition and examine the seasonal succession of the phytoplankton community. Four sampling sites were established: two in Lake Onalaska, a large backwater lake on the Wisconsin side of the main channel; one in the main channel near Dakota, Minnesota; and one in the main channel just upstream from Lock and Dam No. 7.
Keywords: Phytoplankton, Mississippi River.